TERGANGGUNYA PASOKAN PANGAN PALESTINA SEBAGAI AKIBAT DALAM PERANG ISRAEL- PALESTINA MENURUT HUKUM HUMANITER INTERNASIONAL: THE DISRUPTION OF PALESTINIAN FOOD SUPPLY AS AN IMPACTS OF ISRAEL-PALESTINE WAR UNDER INTERNATIONAL HUMANITARIAN LAW - Jamal, Carissa Belia Putri; Khawarizmi, Muhammad Fahreza; Notoprayitno, Maya Indrasti (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2022)
This research discusses and examines how the disruption of Palestinian food supply as a result of genocide committed by Israel against Palestine and the implications that occur as a result of the Genocide. This research is studied from the perspective of humanitarian law, specifically from the 1949 Geneva Convention, which previously explained the importance of food supply which is closely related to food security. This research aims to find out that in the conflict there are attitudes and behaviors of Israel that are contrary to the norms of international humanitarian law, as well as knowing whether the norms of humanitarian law are applied in the conflict and what legal consequences arise from the conflict to Palestine and Israel. The result of the discussion of this research is that Israel has violated several provisions of the Geneva Convention of 1949 concerning the protection of civilians in time of war.